Effect of water ratio and aging time on glass ionomer cement derived from calcium fluoroaluminosilicate-based glass - Ahmad Khiri, Mohammad Zulhasif (2021)
Glass ionomer cement (GIC) is produced from a reaction between calcium fluoroaluminosilicate (CFAS) glass powder and polyacrylic acid (PAA). These kinds of cement are widely used primarily in dentistry for a long time ago for various applications such as adhesive and tooth restorative. In this research, the GIC is designed to perform good in mechanical and antibacterial properties. CFAS glass system is seen as a suitable combination due to its structure similar with natural tooth and ability to release fluoride ions for inhibiting the bacterial growth. The compound of SiO2 and CaO in the glass system have been replaced by waste materials to achieve the usability of waste materials in this research. Soda-lime-silica (SLS) glass and clam shell (CS) are used to act as SiO2 and CaO sources. The SLS-CS-CaF2-Al2O3-P2O5 glass system was used to synthesized CFAS glass by the conventional melt-quench technique and act as a based-glass in the fabricating GIC. In this study, GIC B5 [25SLS-15CS-20CaF2-20Al2O3-20P2O5] with initial ratio of water at 1.2 revealed as the optimum sample based on the physical, structural, mechanical and antibacterial properties. From the mechanical results, the highest Vickers microhardness of GIC B5 is 191.33 HV while the highest compressive strength is 119.14 MPa at 28 days of aging time. Besides that, fluoride release by the GIC B5 was found directly proportional to the aging time between 1 to 28 days and recorded range from 74.62-194.82 ppm. The GIC also shows the antibacterial activity recorded the average diameter of the inhibition zone range between 19.33 and 28.00 mm. The antibacterial activity of GIC shows it is related to the fluoride ion release. It can be concluded that the fluoride release by GIC to the agar medium causes the inhibition of bacteria (S. mutans). Therefore, the GIC derived from CFAS glass in this study has high potential in dental material applications especially GIC B5 sample due to its good physical, structural and mechanical properties as well as its antibacterial activity.